Dinamika Transportasi Modern serta Tantangan Terhadap Angkutan Kota (Angkot) di Jember - Diajeng Anugrah Cantika Sari; Dita Kumalasari; Allya Salsa Bilatul Kh. (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
In the increasingly advanced era of modern transportation, city transportation (angkot) is under high threat. They compete with online transportation that can be ordered via cellphone. Convenience and safety are also considerations why people prefer online motorcycle taxis to public transportation. Moreover, public transportation has travel routes and schedules that often do not suit the interests of the community. This study aims to explain the impact of the role of modern transportation on the decline in the existence of public transportation and the decline in public interest in using public transportation. The method used in this study is qualitative research using an ethnographic approach, namely research carried out by means of observation, interviews and documentation. This research uses conflict theory from Ralf Dahrendrof to strengthen the results of the research. The results of the research show that the impact of the role of online transportation on the shift in the existence of public transportation is very significant. Public interest in using public transportation has greatly decreased. This has caused the income of angkot drivers and angkot owners to decrease drastically, and some angkot are no longer operated because it is difficult to find passengers on these angkot routes. even though on the other hand they have to continue to finance their family's needs which are also increasing. This research is expected to provide a broader understanding of the role of modern transportation in the decline in public interest in public transportation which will be studied using sociological studies.